Ramseyan variations on symmetric subsequences - Verbitsky, O. (Algebra and Discrete Mathematics, 2003)
A theorem of Dekking in the combinatorics of words implies that there exists an injective order-preserving transformation f : {0, 1, . . . , n} → {0, 1, . . . , 2n} with the restriction f(i + 1) ≤ f(i) + 2 such that for every 5-term arithmetic progression P its image f(P) is not an arithmetic progression. In this paper we consider symmetric sets in place of arithmetic progressions and prove lower and upper bounds for the maximum M = M(n) such that every f as above preserves the symmetry of at least one symmetric set S ⊆ {0, 1, . . . , n} with |S| ≥ M.